A SOA-based framework for e-procurement in multi-organisations. (24th May 2010) - Adesina, Aderonke A.; Daramola, J. Olawande; Ayo, Charles K.
The lack of standard platform for application-to-application interaction between the procurement systems of subsidiary organisations of a multi-organisation limits transparency of procurement procedures, and uniformity in the procurement patterns and practices, even when there are cross-cutting concerns. In this paper, an SOA-based e-procurement framework is proposed for effective e-procurement in a multi-organisational context. The e-procurement framework leverages SOA's inherent capability for addressing problems of heterogeneity, interoperability and dynamic requirements. An empirical case study showed that the framework is effective for achieving the corporate goal of promoting transparency, and enhancing uniformity of corporate procurement management in a multi-organisational context.